AKTIVITAS ANTIOKSIDAN DAN KARAKTERISTIK CUKA BUAH MANGROVE PEDADA (Sonneratia alba) - Hardoko, Mr.; Prihanto, Nur Hasyim; Sasmito, Bambang Budi (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2019)
Fruit vinegar is made from fermented fruits using microbes used to make vinegar. The functional properties of fruit vinegar are determined by the type of fruit, the amount of sugar, and the length of fermentation carried out. The purpose of this study was to determine the amount of sugar added and the length of fermentation carried out on the antioxidant activity of pedada mangrove fruit vinegar. The research method used was an experiment of adding sugar (22.5%, 25%, 27.5%, 30%) and fermentation time (5, 7 and 9 days). The results showed that the higher the amount of sugar added tended to increase antioxidant activity, but the length of fermentation carried out could increase antioxidant activity only up to 7 days of fermentation and then antioxidant activity decreased after 7 days of fermentation. The best treatment results were obtained at the 7th day of fermentation and 25% sugar addition with the value of antioxidant activity IC50 48.04 ppm, acetic acid 8.17%, pH 3.13, total phenol 91.3 mgGAE/100g, and vitamin C 104.3 mg /100g.